Knowledge and Practice of Hepatitis B Screening Services Among Pregnant Women in Enugu South Local Government Area (British Journal of Multidisciplinary and Advanced Studies, 2023)
Viral hepatitis is a major global health problem with more than 500 million people chronically infected, causing over 1.4 million deaths per year. The high infection and mortality rate raises questions on the knowledge and practice of hepatitis B screening. The study therefore sets out to examine the knowledge and practice of hepatitis B among pregnant women in Enugu South Local Government of Enugu state. The questionnaire and in-depth interview guide were used as instruments for collection of data from 564 respondents. The quantitative data were analyzed using version 20 of Statistical Package for Social Sciences (SPSS) and frequency distribution tables and percentages were used to present the results. Chi-square (χ²) was used to test the hypotheses; binary logistic regression was used to predict the effect of independent variables on a dependent variable while the qualitative data collected were analyzed in themes as complement to the quantitative data. The Findings of the study revealed that educational status and place of residence have statistically significant relationship with awareness of HBV screening services, while age, income, religion and marital status had no statistically significant relationship with awareness of Hepatitis B screening services. In the same vein, the findings showed that age, level of education, income, and marital status had a statistically significant relationship with utilization of Hepatitis B screening services, while religion and place of residence had no statistically significant relationship with utilization of Hepatitis B screening services. Four hypotheses were tested and three hypotheses were accepted while one was rejected. From the findings in regression analysis it can be seen that in predicting awareness of Hepatitis B screening services, place of residence was statistically significant. Also, age, income level, marital status and level of education were predictors of utilization of HBV screening services.  However, religion was found to have no relationship with the two dependent variables such as awareness of Hepatitis B screening services and utilization of HBV screening services. The study therefore recommends that Government, organizations, institutions, social workers and the general public should be quickly awakened to their separate responsibilities in providing proper information about hepatitis B to the general public focusing on the benefit of utilizing the screening services. This will definitely go a long way in reducing the rate of the occurrence of the disease in this country.